2018
DOI: 10.1088/1361-6560/aae2f4
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to patient specific verification measurements in proton therapy: a comparative experimental study with intentional errors

Abstract: Patient specific verification (PSV) measurements for pencil beam scanning (PBS) proton therapy are resource-consuming and necessitate substantial beam time outside of clinical hours. As such, efforts to safely reduce the PSV-bottleneck in the clinical work-flow are of great interest. Here, capabilities of current PSV methods to ensure the treatment integrity were investigated and compared to an alternative approach of reconstructing the dose distribution directly from the machine control- or delivery log files… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…After the delivery, however, a careful structure revision and correction are necessary. A full plan reoptimisation used in this study (a new spot placement, constraint optimisation [27,28]) has the advantage that it allows for an improved plan quality in case of favourable anatomy and also works in the case of major anatomical changes, where the simpler approach of restoring the dose on the new anatomy independent from the daily structures [67] might fail. As part of the offline quality assurance after the delivery, the delivered DAPT dose can then be reconstructed from the delivery logfile, using the daily CT and a MC dose calculation [30,68], as in such an online workflow, no patient specific dose measurements are possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the delivery, however, a careful structure revision and correction are necessary. A full plan reoptimisation used in this study (a new spot placement, constraint optimisation [27,28]) has the advantage that it allows for an improved plan quality in case of favourable anatomy and also works in the case of major anatomical changes, where the simpler approach of restoring the dose on the new anatomy independent from the daily structures [67] might fail. As part of the offline quality assurance after the delivery, the delivered DAPT dose can then be reconstructed from the delivery logfile, using the daily CT and a MC dose calculation [30,68], as in such an online workflow, no patient specific dose measurements are possible.…”
Section: Discussionmentioning
confidence: 99%
“…At PSI an online DAPT workflow has recently been developed [25] and successfully tested for nondeforming anatomies on a phantom [26]. In the DAPT workflow a daily CT is acquired in treatment position, contours are transferred and a plan is reoptimised online [27], followed by a fast clinical and measurement-free physical quality assurance [28]. After the delivery, the dose is reconstructed on the planning CT [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure and phantoms were modified in our study for motion compensation. Further, Matter et al (56) investigated the capabilities of various plan verification procedures to ensure the integrity of treatment plans under a variety of planning errors. Of the measured errors, two cases were relevant considerations for motion-synchronized deliveries with the M-DDS: the "all spots shifted randomly" case, and the "increase in spot weights" case.…”
Section: Discussionmentioning
confidence: 99%
“…As for fast planning and plan QA, we have previously demonstrated that the complete optimization of plans can be performed in just a few seconds [13], whereas efficient independent dose calculations, based on machine control files, provided a fast and sensitive alternative to plan specific QA measurements [14,33]. Finally, although accurate contour propagation and dose accumulation for deformable geometries are still challenging [34], for the paranasal sinuses spatial transformations between daily datasets are predominantly rigid, simplifying both processes considerably.…”
Section: Patientmentioning
confidence: 99%
“…With DAPT, both the daily anatomy and patient setup variations can be directly included in the daily plan optimization, allowing for reduced margins and irradiation of surrounding healthy tissue. As such, previous studies showed that a highly efficient DAPT workflow including the plan-of-the-day generation and validation might be feasible in less than five minutes after inroom 3D imaging [13,14].…”
Section: Introductionmentioning
confidence: 99%